2022
DOI: 10.3390/molecules27072253
|View full text |Cite
|
Sign up to set email alerts
|

Lithium Ascorbate as a Promising Neuroprotector: Fundamental and Experimental Studies of an Organic Lithium Salt

Abstract: Given the observable toxicity of lithium carbonate, neuropharmacology requires effective and non-toxic lithium salts. In particular, these salts can be employed as neuroprotective agents since lithium ions demonstrate neuroprotective properties through inhibition of glycogen synthetase kinase-3β and other target proteins, increasing concentrations of endogenous neurotrofic factors. The results of theoretical and experimental studies of organic lithium salts presented here indicate their potential as neuroprote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 19 publications
0
4
0
1
Order By: Relevance
“…The “plateau effect” and modulated brain biodistribution was found after lithium salicylate administration that can be associated with absorption, distribution, metabolism, and/or elimination effects from the salicylate anion (Smith et al, 2014). Study of lithium ascorbate biodistribution indicated accumulation of lithium ions in a sort of “depot,” consisting of the brain, aorta, and femur (Torshin et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The “plateau effect” and modulated brain biodistribution was found after lithium salicylate administration that can be associated with absorption, distribution, metabolism, and/or elimination effects from the salicylate anion (Smith et al, 2014). Study of lithium ascorbate biodistribution indicated accumulation of lithium ions in a sort of “depot,” consisting of the brain, aorta, and femur (Torshin et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Twenty male Wistar rats of 5 rats each (n = 5) were divided into four groups consisting of Control (CTR; normal chow), HFr drink; 10 % fructose (w/v), NaB (200 mg/kg) only [ 24 ] and NaB + HFr; 10 % fructose (w/v) given per ostium for six weeks. The rats were given no food overnight (12 h) on the final day of the experiment, and blood glucose levels were measured using a glucometer before sacrifice.…”
Section: Methodsmentioning
confidence: 99%
“…Due to the side effects and toxicity of lithium salts, there is an urgent need to explore non-toxic lithium formulations ( Gitlin, 2016 ; Kakhki and Ahmadi-Soleimani, 2022 ). Lithium ascorbate, which has low acute and chronic toxicity, has been found to mitigate ischemia-induced brain damage and play a significant neuroprotective role ( Torshin et al, 2022 ). In studies on AD, lithium benzoate and lithium cholesterol sulfate have been shown to improve cognitive and memory functions in animal models through multiple pathways ( Hu et al, 2022 ; Lu et al, 2022 ).…”
Section: The History Of Lithium In Medical Researchmentioning
confidence: 99%